2014
DOI: 10.1111/hae.12501
|View full text |Cite
|
Sign up to set email alerts
|

Impact of haemophilia with inhibitors on caregiver burden in the United States

Abstract: Inhibitor development complicates haemophilia treatment and may impact caregiver burden. Compare overall burden of caregivers of children with/without inhibitors in the United States using a novel disease-specific questionnaire and the previously validated CarerQol. An on-line questionnaire with six burden domains (i.e. emotional stress, personal sacrifice, financial burden, medical management, child's pain, and transportation) and three visual analogue scales (VAS) was developed based upon a targeted literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 26 publications
4
33
0
3
Order By: Relevance
“…The strong association between inhibitor development and increased perceived burden for parents of children with haemophilia is not unexpected, and this result is consistent with previous research (DeKoven, Karkare, Kelley, et al, ; DeKoven, Karkare, Lee, et al, ; DeKoven et al, ; Lindvall et al, ; Ljung et al, ). Given this, the HCP must recognise and provide sufficient support to parents of children with inhibitors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The strong association between inhibitor development and increased perceived burden for parents of children with haemophilia is not unexpected, and this result is consistent with previous research (DeKoven, Karkare, Kelley, et al, ; DeKoven, Karkare, Lee, et al, ; DeKoven et al, ; Lindvall et al, ; Ljung et al, ). Given this, the HCP must recognise and provide sufficient support to parents of children with inhibitors.…”
Section: Discussionsupporting
confidence: 91%
“…One likely assumption is that parents of children with current inhibitors might report even higher scores of the HEMOCAB. However, children with past inhibitors could have target joints and chronic pain (Rambod, Forsyth, Sharif, & Khair, ; Vulpen, Holstein, & Martinoli, ) which may increase the burden for the parent (DeKoven, Karkare, Lee, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study comparing the working situation of caregivers from Sweden, UK and Canada, 46% of caregivers of children with inhibitors worked full‐time compared to 59.5% of caregivers of children with haemophilia and 62.7% of caregivers of healthy children . In the United States, DeKoven et al found comparable data; 36.7% of caregivers of children with inhibitors were able to work full‐time compared to 41.6% of caregivers of children without inhibitors due to haemophilia care responsibilities.…”
Section: Discussionmentioning
confidence: 96%
“…Lindvall et al showed increased burden in parents of children with haemophilia and inhibitors compared to caregivers of children with haemophilia only and caregivers of healthy children. DeKoven et al revealed significantly higher caregiver burden in caregivers of children with inhibitors, mainly in the emotional stress and personal sacrifice domains. Caregivers of children with inhibitors showed higher anxiety and stress scores in the EQ‐5D and reported more activity changes on bleed days compared to non‐bleed days in the US DOSE Study .…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in the USA using an online questionnaire with 6 burden domains (emotional stress, personal sacrifice, financial burden, medical management, child's pain and transportation) and 3 visual analogue scales (VAS) reported significantly higher burden in caregivers caring for children with inhibitors …”
Section: Introductionmentioning
confidence: 99%